Environmental, Social, and Governance: A Review of Frameworks, Metrics, and Reporting for Sustainable Development - Mohd Yusof, Ahmad Faizal; Widyasamratri, Hasti (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2025)
Environmental, social, and governance (ESG) aspects have become a key framework for assessing corporate performance, extending beyond traditional financial metrics, emphasizing sustainability, ethical conduct, and long-term resilience. This overview article synthesizes the fundamental elements of ESG and discusses its three pillars: environmental, social, and Corporate Governance. This article also examines the complex landscape of ESG metrics and rating systems, highlighting how differences in vendor criteria and methodologies including metric selection, weighting schemes, data sources, and disclosure verification, lead to significant differences in ESG scores across rating agencies such as MSCI, Sustainalytics, and Refinitiv. Differences in the processing of qualitative and quantitative data, sectoral adjustments, and reliance on self-declarations contribute to inconsistent results and limited comparability. Furthermore, the paper reviews leading global and regional ESG reporting frameworks, including the Global Reporting Initiative (GRI), the Task Force on Climate-related Financial Disclosures (TCFD), the Bursa Malaysia Sustainability Reporting Guidelines, and the Sustainability Accounting Standards Board (SASB), discussing their scope, applicability, and regional implementation. Despite its growing popularity, ESG assessments still face significant limitations, such as inconsistent data quality, a lack of standardization in reporting systems, and potential reporting errors, which undermine the credibility and comparability of ESG assessments. The analysis highlights that effective ESG implementation is crucial for risk management, investor confidence, regulatory compliance, and sustainable value creation, particularly in resource-intensive industries such as construction, manufacturing, and energy.